Effects of reaction temperature and inlet velocity of a bubble column reactor on the bubble size for biodiesel production - Mohd Yusof, Muhammad Nur Amirulhaq; Nasir, Nurul Fitriah (2022)
Bubble column reactors (BCR) are multiphase reactors used in the production of biodiesel. A bubble column reactor can withstand a higher temperature and provide higher efficiency in the process. During the transesterification process in the bubble column reactor, the bubble will be produced and will affect the bubble column reactor performance in biodiesel production. This study aimed to determine the effects of various reaction temperature and inlet velocity in a bubble column reactor on the sizes of the bubble for the transesterification reaction in the production of biodiesel. Different design of perforated plate is also used to find the effects of bubble size. The temperature used are 523 K, 543 K and 563 K and the inlet velocity are 2 m/s, 4 m/s and 6 m/s, respectively. Design and simulation of BCR were performed using SOLIDWORK 2018 ANSYS Fluent. The results obtained show that a drastic changing of gas holdup was found for design A at 563 K and 6 m/s inlet velocity. On the other hand, high circulation pattern occurred on the inlet, outlet, holes of perforated plate, and wall of reactor.